Analisis Penerapan Koreksi Fiskal atas Pendapatan, Beban dan Pajak Tangguhan untuk Menghitung Pajak Penghasilan Terutang Pada PT. Sinar Karya Bahagia - Ainiyah, Nur (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2018)
Differences the principles of accounting (SAK) and tax have a different confession result as well as income and the expense of which is the basis of calculating the PPh corporation, this way commercial finances occount made based on SAK must be adjusted or correction in advance before calculating the amount of taxable income. Fiscal correction is an adjustment in commercial profit and loss process based on terms of tax laws so it has resulting in fiscal profit and loss as the basis of calculating income tax. The aims of this research is to determine the amount of corporate income tax payable with using a fiscal correction of revenue and burder as well as to calculated the value of the different temporary for calculating the amount of taxable income at PT. Sinar Karya Bahagia in 2016.  This research is qualitative with descriptive approach. The finding of this research was showing the total of positive fiscal correction in the amount of RP. 35. 267.375,00 and negative fiscal correction in the amount of Rp. 25.740. 883, 00. It has deffered tax assets in the amount of Rp. 5.962.031,00 and deffered tax liability in the amount of Rp. 4.681.250,00 as well as income tax payable in amount of Rp. 173.081.439,00.  In the account balance was displayed only one, because it was already offsetting before. The resulting differences was occured due to an increase of deffered tax assets in amount of Rp. 1.280.781,00.